Report on isoelectric focusing trial of erythropoietin profiling in two cancerpatients during chemotherapy and darbepoetin treatment - Španinger, Klemen (Acta chimica slovenica, 2011)
The level of erythropoietin, main regulator of erythropoiesis, is affected by hypoxia, anaemia, application of recombinant erythropoietin, chemotherapy and others. Isoelectric focusing (IEF) combined with double immunobloting is a method that enables distinct analysis of endogenous and recombinant erythropoietin isoforms. Aim of our study was to set up analysis of treatment effects on the pattern of endogenous erythropoietin in anaemic breast cancer patient. Urine and blood samples were collected during and after termination of the treatment and analysed by isoelectric focusing. Endogenous erythropoietin was found lower, but still detectable during darbepoetin treatment. Normal shift of erythropoietin isoforms between serum vs. urine, ordinary seen in healthy volunteers, was not observed indicating kidney damage. The patient was suffering from heavy proteinuria and had low Glomerular filtration rate indicating acute renal failure, probably caused by clinical status or cisplatin chemotherapy. IEF has not yet been used for follow up of erythropoietin profile in cancer patients. It enables to monitor the effects of treatment on the level of endogenous erythropoietin and indirectly indicates kidney function.
Keywords: Blood; Breast Neoplasms; Cisplatin; Dojka, novotvorbe; Drug Therapy; Eritrociti, štetje; eritropoeza; Eritropoietin; Eritropoietin rekombinantni; Erythrocyte Count; Erythropoietin; Erythropoietin, Recombinant; Hemoglobini; Hemoglobins; Immunoblotting; Imunoblot; Isoelectric Focusing; Izoelektrični fokusing; Urine